Intervention Model to Increase Muscle Strength in Stroke Patients: A Systematic Literature Review - Haryanti, Hernita Kus; Upoyo, Arif Setyo; Anggraeni, Mekar Dwi (IJNP (Indonesian Journal of Nursing Practices), 2024)
Background: Stroke remains the most common cause of death and disability. Stroke may suffer from several neurological disorders, including hemiplegia, communication disorders, cognitive disorders, and visual-spatial cognitive disorders.Objective: The purpose of this study was to look at how strength training affected stroke patients' muscle strength.Methods: A systematic search for this review used PubMed, ProQuest, Science Direct, Springer Open, Directory of Open Access Journal (DOAJ), and Wiley Online Library using the keywords “strength training (strength training OR strength exercise)” AND “muscle strength” AND “stroke” AND “randomized controlled trial” NOT (systematic review OR meta-analytic). Journals are appraised using the Critical Appraisal Skills Programme (CASP) JBI 2020 the synthesis method used is narrative synthesis. To analyze the agreement between reviewers using the Interclass Correlation Coefficients (ICC) test, with the ICC result being good (r = 0.79; 95% CI, 0.53, 0.92) against the quality assessment of the selected articleResults: 15 articles fully reviewed from 2018-2023. Muscle strengthening exercises are the most effective method for enhancing muscle strength in stroke patients. The research results show that strength training tends to increase the patient’s muscle strength if it is done from the start of a stroke and is carried out for 4-6 weeks of training.Conclusion: The results emphasize the value of strength training regimens for stroke victims in order to avert life-threatening impairment